Changes in aging-induced kidney dysfunction in mice based on a metabolomics analysis - Jiao, Danli; Qi, Li; Hu, Li; Hu, Dan; Li, Xiao; Li, Guona; Li, Zheying; Liu, Shimin; Zhao, Chen; Wu, Huangan (Frontiers in Endocrinology, 2022)
Kidney dysfunction is particularly important in the systemic organ injurious caused by aging.Metabolomics explored the mechanism of kidney dysfunction during aging through the identification of metabolites and characterization of metabolic pathways.In this study, we analyzed serum biochemistry and kidney histopathology of male Kunming mice aged 3 months and 24 months, and found that the aged mice had inflammatory lesions, aggravated fibrosis and functional impairment. High-resolution untargeted metabolomics analyses revealed the endogenous metabolites in kidney and urine of mice were significantly changed by 23 and17, respectively.Pathway analysis of these differential metabolites revealed 6 key signaling pathways, including D-glutamine and D-glutamate metabolism,Purine metabolism,Citrate cycle (TCA cycle) ,Histidine Metabolism, Pyruvate metabolism and Glyoxylate and dicarboxylate metabolism.These pathways were involved in Amino acid metabolism,Carbohydrate metabolism, Nucleotide metabolism, which lead to immune regulation, inflammatory response, oxidative stress damage, cellular dysfunction and bioenergy disorder, and are closely associated with aging and kidney insufficiency.We also screened 9 kinds of sensitive metabolites in urine as potential biomarkers of kidney dysfunction in the aging process,to confirm their therapeutic targets in senior-induced kidney dysfunction and improve the level of risk assessment of senile kidney injury.